Substantiation of Strategic Points for Efficient Functioning of Production Infrastructure of the Southern Region - Taimaskhanov, Khasan Alimsultanovich; Betilgiriev, Maula Abdurahkmanovich; Idigova, Lolita Musaevna; Mintsaev, Magomed Shavalovich; Bataev, Dena Karim-Sultanovich (International Review of Management and Marketing, 2016)
The article analyzes optimal conditions of efficient functioning and strategic development of production infrastructure of the Southern Region. According to the authors, it principally depends on taking into account the specificity of the region when defining the policy of regional authorities, population, and manufacturers. The authors note that the main condition of the production infrastructure development is supporting efficient work of the manufacturing industry. According to the authors, almost all areas and objects of the regional social and production infrastructure require close attention. However, it is possible to predictably include some objects in social and production areas. In the article the authors revealed prerequisites of the development of the essentially new Concept of Developing Infrastructure of the Chechen Republic for the Med-term Perspective within the Strategy of Social and Economic Development of the Chechen Republic till 2020. When creating this Concept of Developing Infrastructure of the Chechen Republic for the Med-term Perspective, the authors took into consideration the whole range of the implemented and developed documents of the federal level, strategies, and programs related to developing industrial ministries and departments. Keywords: production infrastructure, concept of the infrastructure development, the Chechen Republic. JEL Classifications: H54, O10, O18, R13